Eyes Wide Shut: Failures to Teach Student Journalists About Eyewitness Error. (September 2019) - Blom, Robin
Every news story depends on human memory one way or the other; in particular, eyewitness accounts. However, the amount of scholarly research on eyewitness misidentification in the fields of journalism and mass communication is minimal, whereas a plethora of studies is available in other disciplines. Journalism textbooks could fill that void by presenting information about eyewitness issues to student journalists. However, widely adopted journalism textbooks lack in-depth modules, if anything at all, that warn journalism students that they should not take all eyewitness accounts for granted. This essay is a call to increase research in an underdeveloped aspect of journalism education.